1992
DOI: 10.1104/pp.98.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Growth Stimulation by Catecholamines in Plant Tissue/Organ Cultures

Abstract: Addition of catecholamines at micromolar concentrations caused a dramatic stimulation of growth of tobacco (Nicotiana tabacum) thin cell layers (TCLs) and Acmella oppostHffolia "hairy" root cultures. A threefold increase in the rate of ethylene evolution was observed in the catecholamine-treated explants. Aminooxyacetic acid and silver thiosulfate, inhibitors of ethylene biosynthesis and action, respectively, reduced the growth-promoting effect of dopamine. However, these compounds alone could also inhibit the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Recently, they have been noted to promote plant growth and flowering in plants. Dopamine, NE and epinephrine markedly promoted the growth of thin-layer tobacco tissue at micromolar concentrations, while tyramine and phenylethylamine did not (Protacio et al 1992). Three kinds of catecholamines (epinephrine, NE and isoproterenol) promoted flowering under short-day conditions in L. paucicostata 6746, although they did not induce flowering under long-day conditions (Khurana et al 1987).…”
Section: Flower-inducing Activities Of Fn1 and Fn2mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, they have been noted to promote plant growth and flowering in plants. Dopamine, NE and epinephrine markedly promoted the growth of thin-layer tobacco tissue at micromolar concentrations, while tyramine and phenylethylamine did not (Protacio et al 1992). Three kinds of catecholamines (epinephrine, NE and isoproterenol) promoted flowering under short-day conditions in L. paucicostata 6746, although they did not induce flowering under long-day conditions (Khurana et al 1987).…”
Section: Flower-inducing Activities Of Fn1 and Fn2mentioning
confidence: 99%
“…Catecholamines are well known to be involved in neural transmission, and in rapid responses to stress in animals (Protacio et al 1992). Catecholamines and their precursors, such as dopamine, norepinephrine, epinephrine, phenylethylamine and tyramine, are commonly distributed in various kinds of plants (Smith 1977).…”
Section: Flower-inducing Activities Of Fn1 and Fn2mentioning
confidence: 99%
“…A substantial stimulation of growth in cultures of tobacco (Nicotiana tabacum) thin cell layers and Acmella oppositifolia hairy root was achieved by micromolar concentrations of biogenic amines. 26 Synergistic effect of calcium/calcium ionophore on morphogenetic response in M. pudica was observed in M. pudica. Calcium is crucial for plant growth and development as it exerts profound influence on various biological processes.…”
Section: Resultsmentioning
confidence: 97%
“…Results from different in vitro plant systems (Christou and Barton 1989, Kuklin and Conger 1995, Protacio et al 1992 showed that CAs in millimolar concentrations are inhibitory to the growth of plant cultures. Leaves from orchardgrass cultured on SH with 30 p.M dicamba and 1 mM epinephrine turned dark brown ).…”
Section: Morphogenetic Processesmentioning
confidence: 98%
“…Diagnoses of such tumors may be carried out by measurement of CAs or their metabolites in plasma or urine (Feldman et al 1987). Therefore, the importance of knowledge about the CA presence in plants is ac- Protacio et al 1992). …”
Section: Occurrence and Biosynthesis Of Cas In Plantsmentioning
confidence: 99%